Time and Space - do Rosário Monteiro, Maria; Ming Kong, Mário S.; Pereira Neto, Maria João (PHI, 2024)
The texts presented in Proportion Harmonies and Identities (PHI) Time and Space were compiled to establish a multidisciplinary platform for presenting, interacting, and disseminating research. It also aims to foster awareness and discussion on Time and Space, focusing on different visions relevant to Architecture, Arts and Humanities, Design and Social Sciences, and its importance and benefits for the sense of identity, both individual and communal. The idea of Time and Space has been a powerful motor for development since the Western Early Modern Age. Its theoretical and practical foundations have become the working tools of scientists, philosophers, and artists, who seek strategies and policies to accelerate the development process in different contexts.